2012
DOI: 10.2131/jts.37.1017
|View full text |Cite
|
Sign up to set email alerts
|

Nitrergic, glutamatergic and gabaergic systems in lithium toxicity

Abstract: -We examined the role of nitrergic, glutamatergic and gamma-aminobutyric acid (GABA)-ergic systems in the mechanism(s) underlying lithium induced acute toxicity. With this aim, lithium (18 mEq/kg, i.p.) intoxicated rats were observed for 3 hr recording their clinical signs and death. Lithium exposure at the dose used produced central nervous system (CNS) depression. Pre-treatment of N w -nitro-L-arginine methyl ester (L-NAME) a nonselective nitric oxide synthase inhibitor (10 mg/kg, i.p.), 7-nitroindazole (7-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In a high dose, it could also be neurotoxic. It was shown that lithium, administered intraperitoneally in a dose 763.2 mg/kg after 3 hours, caused clinical signs and death in rats [31]. In acute intoxication with lithium administered intraperitoneally by a single nonlethal dose of 250.16 mg/kg, and subchronically, by 4 administrations of 61.904 mg/kg LiCl over the course of 8 days, the vacuolization of the brain tissue and zones of spongiosis were observed in diff erent brain regions, including cerebral cortex, cerebellum, medulla oblongata, mesencephalon, thalamus, and pons [32].…”
Section: Discussionmentioning
confidence: 99%
“…In a high dose, it could also be neurotoxic. It was shown that lithium, administered intraperitoneally in a dose 763.2 mg/kg after 3 hours, caused clinical signs and death in rats [31]. In acute intoxication with lithium administered intraperitoneally by a single nonlethal dose of 250.16 mg/kg, and subchronically, by 4 administrations of 61.904 mg/kg LiCl over the course of 8 days, the vacuolization of the brain tissue and zones of spongiosis were observed in diff erent brain regions, including cerebral cortex, cerebellum, medulla oblongata, mesencephalon, thalamus, and pons [32].…”
Section: Discussionmentioning
confidence: 99%